Integrated assessment of environmental and economic sustainability in natural and conventional vegetable farming systems in the Indian Himalayas - Riya, T; Subhash, S; Anmol, N; Satish, P V; Nidhi; Akanksha, K; Anurita, K (Plant Science Today, 2026)
Natural farming (NF) is gaining global attention as an agroecological farming approach to address the dual aspects of ecological benefit and maintaining food security. The present study examined the impact of NF compared to conventional farming (CF) among vegetable growers in the hilly region of India. The study was performed with 300 actively engaged farmers selected through a multi-stage sampling technique to quantify various environmental indicators like Greenhouse Gas (GHG), acidification, eutrophication, ecotoxicity and ecoefficiency with TEBA-TCA and IPCC Tier 1 framework. In particular, NF significantly reduced environmental footprints, with net GHG emissions decreasing from 8215.6 kg CO₂ eq./ha in conventional farming to just 69.2 kg CO₂ eq./ha, while eco-efficiency improved from ₹36.6−₹7163/kg CO₂ eq. Findings further revealed that NF-based crop combination achieved a higher benefit-cost ratio of 7.51, reflecting its strong economic viability. Comparing the composite sustainability impact with aggregation, suggested NF combinations significantly reduce the average emission value (e.g., 69.2 kg CO₂ eq./ha in NF vs. 8215.6 kg CO₂ eq./ha in CF for tomato). While the other indicators of ecotoxicity, eutrophication and acidification, reported no evidence through their eco-friendly farm management practices, remarking on the resilient balancing between mitigating climate change and ensuring farm profitability. Overall, the enhanced eco-efficiency observed in NF supports a higher sustainability index, demonstrating that integrating environmental externalities into economic assessments can guide sustainable farming strategies in alignment with the Sustainable Development Goals (SDGs).